FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM MENGGUNAKAN BENIH JAGUNG HIBRIDA DI KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Hasmari Noer; Idris; Jumardin; Abdul Rasit (Jurnal Agrotech, 2020)
This research aims to determine the factors that influence farmers' decisions in using hybrid maize seeds. This research was conducted from July to August 2019 in Sigi Biromaru District, Sigi Regency, Central Sulawesi Province. This research was conducted using a survey method. The determination of the research location was carried out by means of purposive sampling. based on this area the majority of the population is corn farmers. Respondents were determined using the Multistage Random Sampling method, through the following stages, determining the location, determining the farmer groups in each sample village, determining five respondents from each village, in order to obtain a total sample of 20 farmers. The results showed that the factors of age, education, land area, capital, length of farming, extension and access to production facilities together or partially did not have a significant effect on farmers' decisions to use hybrid maize seeds in Sigi Biromaru District, Sigi Regency.